Observation of the B0s → J/[psi]K0SK+-π-+ decay - Aaij, Roel; Bachmann, Sebastian; Bien, Alexander; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; Färber, Christian; Gersabeck, Evelina; Grillo, Lucia; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Journal of high energy physics, 2014)
Decays of the form B(s)0 → J/ψKS0h+h(′) −(h(′) = K, π) are searched for in proton-proton collision data corresponding to an integrated luminosity of 1.0 fb−1 recorded with the LHCb detector. The first observation of the Bs0 → J/ψKS0K±π∓ decay is reported, with significance in excess of 10 standard deviations. The B0 → J/ψKS0K+K− decay is also observed for the first time. The branching fraction of B0 → J/ψKS0π+π− is determined, to significantly better precision than previous measurements, using B0 → J/ψKS0as a normalisation channel. Branching fractions and upper limits of the other B(s)0 → J/ψKS0h+h(′) − modes are determined relative to that of the B0 → J/ψKS0π+π− decay.
*The LHCb collaboration: R. Aaij, S. Bachmann, A. Bien, A. Comerma-Montells, M. De Cian, F. Dordei, S. Esen, C. Färber, E. Gersabeck, L. Grillo, X. Han, S. Hansmann-Menzemer, A. Jaeger, M. Kolpin, K. Kreplin, G. Krocker, B. Leverington, J. Marks, M. Meissner, M. Neuner, T. Nikodem, P. Seyfert, S. Stahl, U. Uwer, M. Vesterinen, S. Wandernoth, D. Wiedner, A. Zhelelov [und sehr viele weitere Personen]
Im Titel sind die Zahl 0 und die Zeichen + und - hochgestellt
Im Titel ist der Buchstabe s tiefgestellt
Im Titel ist "psi" als griechischer Buchstabe dargestellt
Gesehen am 29.07.2020